Digital is New Normal: Makna Konvergensi Media Bagi Mahasiswa Gen Z UIN Sumatera Utara - Fadillah, Annisa; Angkat, Darni; Anggraini, Novi; Manurung, Afwan Syahril (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The advancement of digital technology has accelerated media convergence, integrating traditional and digital media into a unified and interconnected communication ecosystem. This phenomenon not only transforms the distribution of information but also reshapes how individuals think, interact, and construct their identities, particularly among Generation Z. This study aims to explore the meaning of media convergence from the perspective of Generation Z students at the State Islamic University of North Sumatra (UIN Sumatera Utara). Employing a descriptive qualitative approach, data were collected through semi-structured interviews with five informants selected via purposive sampling. The findings reveal that students perceive media convergence as a new normal embedded in their daily lives. Digital media are viewed not merely as tools but as integral spaces for learning, self-expression, and social interaction. Four major themes emerged: efficiency and accessibility of information, digital lifestyle transformation, creative and identity expression, and awareness of ethical digital challenges. The novelty of this study lies in its focus on the subjective experiences of students within a faith-based higher education setting. These findings enrich the discourse on digital literacy and offer strategic implications for educational institutions in cultivating a generation that is adaptive, critical, and ethically responsible in navigating the digital media landscape.